A143: Barriers to Referral to Pediatric Rheumatology among General Pediatricians in the Upper Midwest. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Correll, Colleen K.; Spector, Logan G.; Zhang, Lei; Binstadt, Bryce A.; Vehe, Richard K.
Abstract : Background/Purpose: Access to pediatric rheumatology (PR) care is limited. An average of 28 fellows graduate from PR training programs annually, and there are 224 board‐certified pediatric rheumatologists in the United States. Eleven states have no pediatric rheumatologist and 24 states have two or fewer. Furthermore, the mean distance to a certified pediatric rheumatologist is 60 miles. The impact that limited access to PR has on general pediatricians has not been studied. Methods: A web‐based survey was emailed to general pediatricians practicing in Minnesota (MN), North Dakota (ND), and South Dakota (SD). The email databases were obtained from the MN and ND state medical licensing boards and from the SD chapter of the American Academy of Pediatrics. The goal of the survey was to define barriers to access to PR care and the consequences of limited access. Basic descriptive analysis was performed and responses were summarized. Results: The overall response rate was 15.3% (93/609). Responders were younger than non‐responders (mean age 48 yo versus 53 yo, p = 0.0006) and had been in practice a shorter period of time (mean 22 y versus 27 y, p = 0.0051). Forty percent (37/92) of the clinics were urban, 40% (37/92) suburban, and 20% (18/92) rural. Twenty‐nine percent (27/92) of respondents' clinics were at least two hours by car from a pediatric rheumatologist, and 9% (8/92) were more than 6 hours away. Ninety‐two percent (85/92) had referred a patient to PR at least once, but 89% (83/93) had experienced a situation at least once in which they considered a referral to PR but ultimately did not. Reasons for not referring varied. When asked, "In cases in which you considered a PR referral but did not refer a patient to a pediatric rheumatologist, please indicate your reasons for doing so. (Select all that apply), " many had referred to other subspecialists instead: 29% (24/83) to pediatric infectious disease, 20% (17/83) to adult rheumatology, and 12% (10/83) to pediatric orthopedics, while 34% (28/83) managed the patient themselves. Although not a pre‐specified choice in the survey, 9% (3/32) of pediatricians added wait‐time as the reason for not referring to PR. Thirty‐five percent (32/60) had referred a pediatric patient to an adult rheumatologist, most commonly for distance (47%), while physician preference was never selected as a reason. Conclusion: Pediatricians often refer children with possible rheumatic disease to specialists other than PR due to reasons of distance and wait‐time. Referral to adult rheumatologists occurs, but not based on pediatrician preference. These findings suggest that the PR workforce is inadequate to meet demand, at least in the Upper Midwest. Interventions are needed to improve access to care in PR.